Kajian Metode Penalti Pada Optimisasi Linear Dengan Kendala Nonlinear - Siddik, Fajar Erin; Nababan, Esther Sorta Mauli; Sawaluddin, Sawaluddin; Zahedi, Zahedi (Universitas Islam Sumatera Utara, 2024)
This research aims to examine the penalty methods used in linear optimization. The main objective is to identify the advantages and disadvantages of each penalty method, as well as determine the specific context in which each method is most effective. This research belongs to the literature research type. The study is conducted on prepared cases to obtain the optimal result of each penalty method. Penalty methods and barrier methods are interrelated in optimization, especially in handling problems with constraints. The penalty method is used to start the solution search, while the barrier method is applied at the final stage to refine the solution. This is because the penalty method is able to provide an initial solution quickly, which can then be refined using the barrier method to better approach the constraint boundary.